An in vitro study on the inhibition and ultrastructural alterations of Candida albicans biofilm by zinc oxide nanowires in a PMMA matrix - Constanza Apip; Alejandra Martínez; Manuel Meléndrez; Mariana Domínguez; Teresita Marzialetti; Ricardo Báez; Gabriela Sánchez-Sanhueza; Andrés Jaramillo; Alfonso Catalán (Elsevier, 2021)
Objectives: The purpose of this study was (i) to investigate whether nanocomposite poly(methyl-methacrylate)-zinc oxide nanowires (PMMA-ZnO-NWs) have C. albicans antibiofilm activity; (ii) to evaluate the interaction between components of the nanocomposites based on PMMA-ZnO-NWs by Raman spectroscopy; and (iii) to assess ultrastructural alterations. Design: Sixty-eight rectangles (17 PMMA (control) and 51 PMMA-ZnO-NWs (250, 500, 1000 ppm ZnO nanowires) were fabricated. C. albicans ATCC 10231 and a C. albicans clinical strain were tested. Adherence, biofilm formation and ultrastructural alterations were assessed by transmission electron microscopy. Raman mapping images and spectra were analyzed using main component analysis. Results: Nanocomposite PMMA-ZnO-NWs inhibited the formation of C. albicans biofilms 94% at 1000 ppm and 80% at 500 ppm against both C. albicans strains. PMMA-ZnO-NWs induced ultrastructural alterations, including cell wall damage and disorganization of the cytoplasmic membrane, resulting in cell lysis. Raman spectroscopy showed new vibrational modes (300-365-485-600 cm−1) for PMMA and ZnO-NW interactions. Conclusions: PMMA-ZnO-NWs inhibited C. albicans dose-dependent biofilm formation and led to changes in the structures and cell membrane. Raman spectroscopy showed chemical interactions between ZnO-NWs and PMMA, as suggested by the appearance of new bands at 301 and 485 cm−1.